Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fimmu.2019.03070
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Crosstalk Between Myeloid-Derived Suppressor Cells and Regulatory T Cells in Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a fatal disease with rising incidence and a remarkable resistance to current therapies. The reasons for this therapeutic failure include the tumor's extensive infiltration by immunosuppressive cells such as myeloid-derived suppressor cells (MDSCs) and regulatory T cells (Tregs). By using light sheet fluorescent microscopy, we identified here direct interactions between these major immunoregulatory cells in PDAC. The in vivo depletion of MDSCs led to a significant redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 33 publications
4
99
0
Order By: Relevance
“…Next to the immunosuppressive effects conferred by soluble mediators and leukocyte receptor interactions, the extensive infiltration of the tumor by immunosuppressive cell populations, such as tumor-associated macrophages (TAM) [ 16 , 17 ], myeloid-derived suppressor cells (MDSC) [ 18 ], and regulatory T cells (Treg) [ 19 , 20 ], has been identified as a major driver of the pro-tumorigenic transformation in the TME. The presence of these immunosuppressive cells hampers effector T cell induction and recruitment as well as the capability of both natural killer (NK) cells and antigen-presenting cells (APC) to exert effective tumor surveillance, consequently leading to a profound inhibition of the anti-tumor immune response [ 21 ]. Thus, the understanding of this immunosuppressive network mediating tumor immune evasion, via cell–cell interactions and by the secretion of soluble immunomodulatory mediators, is essential for the development of novel strategies overcoming immune resistance in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to the immunosuppressive effects conferred by soluble mediators and leukocyte receptor interactions, the extensive infiltration of the tumor by immunosuppressive cell populations, such as tumor-associated macrophages (TAM) [ 16 , 17 ], myeloid-derived suppressor cells (MDSC) [ 18 ], and regulatory T cells (Treg) [ 19 , 20 ], has been identified as a major driver of the pro-tumorigenic transformation in the TME. The presence of these immunosuppressive cells hampers effector T cell induction and recruitment as well as the capability of both natural killer (NK) cells and antigen-presenting cells (APC) to exert effective tumor surveillance, consequently leading to a profound inhibition of the anti-tumor immune response [ 21 ]. Thus, the understanding of this immunosuppressive network mediating tumor immune evasion, via cell–cell interactions and by the secretion of soluble immunomodulatory mediators, is essential for the development of novel strategies overcoming immune resistance in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations in different cancer models suggest a crosstalk between MDSC and Treg, but its character remains incompletely defined [ 21 , 22 , 23 ]. As the crosstalk between MDSC and Treg has recently been proposed to be a powerful barrier counter-acting anti-tumoral immune responses, this review is dedicated to give insights into the potential role of cell–cell contacts as a prerequisite for the immunosuppressive mechanisms in the TME, leading to tumor immune evasion.…”
Section: Introductionmentioning
confidence: 99%
“…The PD-L1/PD-1 interaction, in turn, leads to the suppression of T-cell activation and self-tolerance [ 65 ]. In addition, MDSCs have been shown to stimulate the expansion of immunosuppressive regulatory T cells (Tregs) through the IL-10-dependent secretion of TGF-β and IFN-γ [ 66 , 67 ], again resulting in suppression of the T cell function. Consequently, the targeted depletion of MDSCs in GEMMs by different experimental strategies has been demonstrated to activate an effective endogenous antitumor T cell response in established tumors and to significantly impair Kras G12D -driven pancreatic cancer initiation when induced at early stages [ 68 , 69 ].…”
Section: Role Of Innate Immune Cells In Pdac: Macrophages and Myelmentioning
confidence: 99%
“…Another study from this same group later demonstrated that CD40 expression on MDSCs is required for Treg induction, since adoptive transfer of CD40-deficient MDSCs or administration of anti-CD40 antibodies fails to induce Tregs ( 89 ). Treg induction by MDSCs is attenuated in the Transwell system that separates the two cell types, suggesting the requirement of direct cell-to-cell contact ( 90 ). In a murine model of B-cell lymphoma, MDSCs promoted the expansion of Tregs from pre-existing natural Tregs but not conversion from naïve T cells.…”
Section: Suppressive Mechanisms and Cell Targets Of Mdscsmentioning
confidence: 99%